Generic drug prescribing in primary care: A nationwide analysis - AKICI, AHMET (WILEY, 2021)
Introduction Dissemination of generic drug (GD) use could provide significant savings on drug expenditures and contribute to the long-term sustainability of healthcare. We aimed to exhibit the nationwide trend of GD use in primary care and investigate potentially relevant drug and patient factors. Methods Prescriptions written by primary care physicians in Turkey between 2013 and 2016 were analysed using the National Prescribing Information System. We determined the ratio of GD prescriptions with all prescriptions in terms of quantity and cost. In addition, we analysed the use of GD in terms of demographic characteristics of the patients, the most frequently prescribed preparations and frequent indications. Results In the 4-year period, we identified 518,335,821 prescriptions, those with at least one GD constituted 54.0% (n = 786,972,813) with a total cost-share of 36.9%-37.8%. GD use was the highest in 2016 (54.4%) and lowest in 2014 (53.6%). GD prescribing was higher in women than men every year (P < .001 for each), with the highest difference in 2016 as 54.7% vs 54.0%. GD utilisation decreased as the age group increased, which was 64.0%-64.5% in <18-year-old group and 46.0%-47.1% in >= 75-year-old group. Among the top ten encountered indications, the highest and lowest GD prescribing was detected in acute tonsillitis (68.1%) and hypertension (33.9%). Metformin had the highest percentage of GD prescribing (96.1%-97.7%), whereas esomeprazole showed the lowest GD prescribing (4.5%-14.8%) among the most frequently used preparations in primary care. Conclusion This study shows a modest upward trend of GD utilisation in primary care, though its share appears to be lower than expected. GD use revealed a consistent reduction towards older age groups. GDs were more likely to be prescribed for acute conditions, particularly infectious diseases.
Keywords: BRAND-NAME STATINS; PERCEPTIONS; MEDICINES; DISEASE; THINK